Teachers' beliefs and understandings of literacy in the pre-school : Pre-school Literacy Project Stage 1 - Ure, Christine; Raban, Bridie (Contemporary issues in early childhood, 2001)
The role of literacy during the pre-school years is argued from evidence found in the international research literature and provides the starting point for exploring the beliefs and understandings of staff in 38 sessional pre-schools and two long-day childcare centres that included sessional pre-school programmes in Victoria. These professionals were found to be uncertain about their role with respect to young children's early literacy development, but they were keen to increase their knowledge and develop appropriate practice within the contexts of their centres. Reasons for these findings are explored. In particular, the distinction between literacy as social practice and literacy as reading and writing skill demarcated the understandings and practical implications for these pre-school teachers. [Author abstract, ed]